2016
DOI: 10.3389/fmicb.2016.00527
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-nitzschia Challenged with Co-occurring Viral Communities Display Diverse Infection Phenotypes

Abstract: Viruses are catalysts of biogeochemical cycling, architects of microbial community structure, and terminators of phytoplankton blooms. Viral lysis of diatoms, a key group of eukaryotic phytoplankton, has the potential to impact carbon export and marine food webs. However, the impact of viruses on diatom abundance and community composition is unknown. Diatom-virus dynamics were explored by sampling every month at two coastal and estuarine locations in Washington state, USA resulting in 41 new isolates of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…For example, it has been shown that virus infection can drive haplotypic differentiation of phytoplankton and that host ASV variation is relevant for protection against the virus (Needham et al, 2017). The existence of Pseudo-nitzschia viruses has been demonstrated (Carlson et al, 2016) and also recently isolated from the GoT (unpublished data), while strain specificity for viral infections has also been demonstrated and is common in diatom viruses (Nagasaki et al, 2004). Another commonly observed pattern in metabarcoding data is that more common taxa tend to be more microdiverse (Needham et al, 2017;Ruggiero et al, 2022).…”
Section: Rbcl Metabarcoding As a Population-genetics Toolmentioning
confidence: 99%
“…For example, it has been shown that virus infection can drive haplotypic differentiation of phytoplankton and that host ASV variation is relevant for protection against the virus (Needham et al, 2017). The existence of Pseudo-nitzschia viruses has been demonstrated (Carlson et al, 2016) and also recently isolated from the GoT (unpublished data), while strain specificity for viral infections has also been demonstrated and is common in diatom viruses (Nagasaki et al, 2004). Another commonly observed pattern in metabarcoding data is that more common taxa tend to be more microdiverse (Needham et al, 2017;Ruggiero et al, 2022).…”
Section: Rbcl Metabarcoding As a Population-genetics Toolmentioning
confidence: 99%
“…4). Ten were associated with species previously reported along the US Pacific Coast based on reference sequences available in GenBank and prior studies using ARISA (Carlson et al, 2016; Hubbard et al, 2014, 2008; Smith et al, 2018b). Half were putatively identified based on prior observations as P. australis/P.…”
Section: Resultsmentioning
confidence: 99%
“…Globally sampled populations of P. pungens were found to exhibit strong isolation by distance, however, time-series samples were pooled by region (Casteleyn et al, 2010), potentially masking relevant temporal shifts which have been repeatedly identified in other marine diatoms (Godhe and Härnström, 2010; Rynearson et al, 2006; Whittaker and Rynearson, 2017). Interestingly, morphologically and genetically distinct P. pungens varieties have been identified along the US West Coast (Carlson et al, 2016; Hubbard et al, 2014, 2008; Villac and Fryxell, 1998). Here we show that not only do allele frequencies show temporal shifts, in some instances these shifts correlate to some extent with the presence of DA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Globally sampled populations of P. pungens were found to exhibit strong isolation by distance, however, time-series samples were pooled by region (Casteleyn et al, 2010), potentially masking relevant temporal shifts which have been repeatedly identified in other marine diatoms (Godhe and Härnström, 2010;Rynearson et al, 2006;Whittaker and Rynearson, 2017). Interestingly, morphologically and genetically distinct P. pungens varieties have been identified along the US West Coast (Carlson et al, 2016;Hubbard et al, 2014Hubbard et al, , 2008Villac and Fryxell, 1998). Here we show that not only do allele frequencies show temporal shifts, in some instances these shifts correlate to some extent with the presence of DA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…blooms using ARISA Seventeen distinctly-sized amplicons were observed with ARISA (Fig.4). Ten were associated with species previously reported along the US Pacific Coast based on reference sequences available in GenBank and prior studies using ARISA(Carlson et al, 2016;Hubbard et al, 2014Hubbard et al, , 2008Smith et al, 2018b). Half were putatively identified based on prior observations as P. australis/P.…”
mentioning
confidence: 99%